ANALYSIS OF EFL STUDENTS’ DIFFICULTIES IN WRITING AND COMPLETING ENGLISH THESIS - Fitria, Tira Nur (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The objective of this research is to know the EFL students’ difficulties in writing and finishing their thesis. This research employs descriptive qualitative research. From the result analysis of a questionnaire, there are internal and external factors of EFL students’ difficulties in writing and finishing a thesis. In internal factors are 1) difficulty in choosing the title of the English title, 2) feeling bored, pessimistic, bored/saturated, and doubtful with their abilities, 3) feeling fears or worries during the proposal seminar exam or thesis examination later, 4) having a health problem or down, 5) students’ disability in understanding the systematics of writing a thesis, 6) tending to use online translation tools, 7) having difficulty in using English grammar, choosing the right vocabulary, spelling, and punctuation correctly. The students’ difficulty in writing and completing a thesis shows that the most difficult parts are in chapter 4 (result/findings and discussion). While external factors are 1) having communication problems with supervisors, for example, lecturers are difficult to contact, reply to messages for a long time, or do not reply to messages. 2) having problems with supervising lecturers’ writing, for example, writings cannot be read clearly or be understood. 3) having difficulty in finding references on the internet, 4) there are no complete reference sources and no free access to digital libraries on campus, 5) technical problems on devices such as laptops/computers, 6) having cost or financial problems and personal problems during the process of working on and completing the thesis. 7) students’ surrounding environment is not/less conducive. But, have a part-time job, have a busy life with hobbies or personal pleasures, and have a busy life in organizations both on and off-campus. do not influence them in working on and completing the thesis.